Neurotechnology methods, advances and applications - Albuquerque, Victor Hugo C. de; Athanasiou, Alkinoos; Ribeiro, Sidarta (The Institution of Engineering and Technology, 2020)
This book focuses on recent advances and future trends in the methods and applications of technologies that are used in neuroscience for the evaluation, diagnosis and treatment of neurological diseases and conditions or for the improvement of quality of life
Keywords: Electronic books